A Study of the Effects of First Person versus Third Person View in Educational Animation - H. N. Dib; N. Adamo-Villani; J. Yu (European Alliance for Innovation (EAI), 2015)
The paper reports a study that investigated the effect of egocentric versus exocentric view in an educational animation whose goal was to teach undergraduate students the various tasks that a construction manager performs in the field. Specifically, the study aimed to determine the effect of perspective view on students' subject learning and preference. Findings show that while students have a preference on perspective view, the perspective view does not have a significant effect on students' learning outcomes.